Teaching Reading with Authentic Texts about Computers Using the Bottom Up Strategy - Mauloeddin Afna (Universitas Syiah Kuala, 2015)
This experimental research was aimed at finding out whether there was a significant difference in the achievements of students who were taught through the Bottom Up Strategy (BUS) for teaching reading comprehension using authentic texts about computers and those who were taught through the conventional way (i.e. teacher-centered). The reading comprehension was built up from three inputs: comprehension, meaning construction, and understanding of technical terms. The study relied on a decoding process of outlining the paragraph into a line of idea organization. The decoding process is easily applicable because authentic texts about computer features and computer applications were used in the teaching process. The Department of Information Technology of the Aceh Polytechnic, Banda Aceh, a vocational training institute with majors in computer information systems, was selected as the research location for this study. After 10 meetings or treatments, the t-score of the experimental class (EC) was 13.76 while the t-score of the control class (CC) was 12.48. The value of t-table at a level of significance (α) 0.05 was 1.70 (t (0.95) (30) = 1.70), Thus there was a significant difference between EC and CC in their reading comprehension achievements. By comparison of scores via 13.76 12.48, it is concluded that there was a significant difference in the achievements between the two classes, thus, Ha is proved to be accepted for this study, that is using BUS for teaching reading comprehension using authentic texts about computers is more effective.